2001
DOI: 10.1620/tjem.193.207
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Distribution of Total Low Km Cyclic AMP Phosphodiesterase in Mouse, Rat and Rabbit Kidney.

Abstract: The activity of cAMP degradation enzyme, cAMP phosphodiesterase (cAMP PDE), in renal tubules is a critically important factor in determining cellular cAMP levels, particularly in response to hormones. In this study we examine the nephron distribution of cAMP PDE activity in the mouse, rat and rabbit kidney and important cellular regulators of cAMP PDE, namely calmodulin and adenosine triphosphate (ATP). We assayed total low Km cAMP PDE in microdissected tubule segments, using 10(-6) M (3H) cAMP as a substrate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The renal phenotype of Pkd1 or Pkd2 heterozygous knockout mice is similarly normal or very mild; unfortunately, no Pkd1 or Pkd2 rat model currently exists (21). Furthermore, in previous studies, we and others (12,27) reported higher PDE activities in kidneys from mice compared with those from rats. Since the hydrolytic capacity of PDEs far exceeds the maximum rate of synthesis by adenylyl cyclases, cellular levels of cAMP may be more sensitive to changes in PDEs compared with those in adenylyl cyclases.…”
Section: Pkd2mentioning
confidence: 79%
“…The renal phenotype of Pkd1 or Pkd2 heterozygous knockout mice is similarly normal or very mild; unfortunately, no Pkd1 or Pkd2 rat model currently exists (21). Furthermore, in previous studies, we and others (12,27) reported higher PDE activities in kidneys from mice compared with those from rats. Since the hydrolytic capacity of PDEs far exceeds the maximum rate of synthesis by adenylyl cyclases, cellular levels of cAMP may be more sensitive to changes in PDEs compared with those in adenylyl cyclases.…”
Section: Pkd2mentioning
confidence: 79%
“…Given the multiplicity of its actions in cells, calmodulin likely plays other physiologically significant roles in the IMCD. One such role is stimulation of phosphodiesterase activity, which has been demonstrated in prior studies (49,50). The potential attenuation of the cAMP response via CaM-sensitive phosphodiesterase-1 has not been addressed in this study.…”
Section: Discussionmentioning
confidence: 91%
“…14,15 PDE1 accounts for most of the PDE activity in renal tubules 16,17 and is the only PDE activated by calcium 14,15 (which is reduced in PKD cells), and its activity is reduced in cystic kidneys. 17 Furthermore, the pool of cAMP generated in response to vasopressin (the main adenylyl cyclase agonist in collecting duct and distal nephron 18 ) is mainly hydrolyzed by PDE1, and the accumulation of cAMP in response to vasopressin is markedly increased when intracellular calcium is reduced, mainly because of lower PDE1 activity.…”
Section: /Ws25mentioning
confidence: 99%
“…35 A possible explanation for the different susceptibility of mice and rats to the development of PKD and the cystogenic effects of DDAVP could be the higher PDE activities reported in kidneys from mice compared with those from rats. 16,17 To test this hypothesis, we administered DDAVP (30 ng/100 g body wt per hour subcutaneously using a osmotic minipump) to and Pkd2 2 /WS25 ;Pde3b 2 /2 mice had slightly higher body and liver weights but no increase in liver cystic or fibrotic indices. These results are consistent with the hypothesis that PDE3 activity limits the cystogenic effect of DDAVP in mouse models of PKD.…”
Section: /Ws25mentioning
confidence: 99%